AKUNTABILITAS KEUANGAN PADA BADAN PERENCANAAN PEMBANGUNAN DAERAH KABUPATEN PARIGI MOUTONG - Seniwati, Seniwati; Mufti, Muh. Irfan; Kurnia, Intam (Katalogis, 2018)
Financial Accountability for Regional Development Planning Agency Parigi Moutong district still can not be rated successful achievement performance. It is characterized by the presence of some of the findings by the State Audit Board 2015.Tujuan year to be acquired on the outcome of this study is to Know the application of financial accountability in Regional Development Planning Board Parigi Moutong district. This study used a qualitative approach to the selection techniques with the number of informants purposively selected informants as many as four people. Data was collected through interviews, observation and documentation. The data analysis technique is inductive Penelitiakan build their research conclusions by means of abstract empirical data it collects from the field and look for patterns that may be in the data-datat ersebut. The theory used is the theory proposed by Nordiawan, Sandi Putra (2007), the form (normative measures that need to be realized in the accounting information) with the variables in the form of relevant, reliable, comparable and understandable. The results showed that the Financial Accountability in Regional Development Planning Agency Parigi Moutong not fully implemented in accordance with the vision and mission. Applications SAI applied with the application of Information and Communication Technology (ICT) saatini led to the principle of the preparation and presentation of financial statements is relevant, reliable, comparable and understandable, has not been implemented optimally. So that their misuse by some budget manager who later became the findings by the State Audit Board.